Development, validation and application of a high-performance liquid chromatography method for the detection of ibuprofen in elephant plasma - Sherry Cox; Aaron Bloom; Riley Golias; Madeline Duncan; Joan Bergman; Andrew Cushing (Heliyon, 2024)
A simple and accurate method for the determination of ibuprofen concentrations in elephant plasma was developed and validated using reverse phase high-performance liquid chromatography (HPLC). Utilizing a liquid-liquid extraction with ethyl acetate, methanol, and phosphoric acid, samples were separated on an XBridge C18 column. The mobile phase consisted of 0.005 M ammonium phosphate and acetonitrile (40:60, v/v). Both ibuprofen and the internal standard flurbiprofen were quantitated using an ultraviolet (UV) detector set at 214 nm. The lower limit of quantification (LLOQ) was 0.05 μg/mL in 100 μL of plasma. The average recovery was over 95 % while the intra-assay variability ranged from 0.8 to 9.9 % and the inter-assay variability ranged from 2.7 to 9.8 %. The method was used successfully in a therapeutic drug monitoring program for elephants and could be used in future pharmacokinetic studies.